Advantages of modified stoppa Vs ilioinguinal approach in acetabular injuiry - Shariff, Mohammad Yusoff; Applanaidu, Ramesh Naidu; Ahmad, Abdul Rauf; Mor Japar Khan, Ed Simor Khan (Malaysian Orthopaedic Association, 2018)
Introduction • Acetabular surgery is known for its complexity • It requires high level of expertise and ideally done at a specialized trauma centre • Anterior approach in acetabular surgery is done via • Classical ilioinguinal approach • Modified stoppa approach